Translation Techniques and Methods of Cultural Terms in the Video Game Selera Nusantara : Chef Story (English Language and Literature (JELL), 2026)
This study aims to analyze techniques and methods applied in the translation of cultural terms in the video game Selera Nusantara: Chef Story. The research employed a qualitative descriptive approach. The data were collected from the in-game text aspects by tabulating and identifying the cultural terms. There were 278 cultural terms collected. The terms were then analyzed by using the framework proposed by Molina and Albir (2002) for translation techniques and by Newmark (1988) for translation methods. The results show that there are 577 techniques found, with borrowing (145 data), established equivalent (138 data), generalization (98 data), and reduction (66 data) as the most dominant techniques. Collectively, these techniques represent 77.47% of the tendency toward communicative translation method. The high frequency of borrowing technique positions the translation within the spectrum of communicative translation. It retains cultural identity, while the other three techniques ensure comprehensible and effective translation. This study highlights the importance of bridging cultural gap by balancing cultural preservation and comprehensibility in video game translation.
Keywords: Translation Techniques; Translation Methods; Cultural Terms; Video Game